Strategi Optimalisasi Daya Saing Bank Syariah Pasca Merger Bank-Bank Syariah BUMN - Hendri Hermawan Adinugraha (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2023)
Mergers are an important part of restructuring financial operations and increasing opportunities to increase the share of the Sharia banking market in Indonesia. This study aims to analyze the strategy for optimizing the competitiveness of Islamic banks after the merger of state-owned Islamic banks. This type of research uses field research. This research approach uses qualitative. The research setting is located at Bank BSI KC Pekalongan Pemuda. The subject of this research is Bank Syariah Indonesia (BSI) KC Pekalongan Pemuda, namely the Branch Operations and Service Manager and Marketing Financing at BSI KC Pekalongan Pemuda. The main sample of this research data source is informants consisting of employees and customers of Bank BSI. The data collection technique uses the trinulation technique which is a combination of observation, interview, and documentation techniques. Data analysis used a data credibility test with triangulation techniques from different data. Analysis of the data used in the study used interactive model data analysis by Miles and Huberman. The results of this research conclude that Bank Syariah Indonesia officially carried out a merger on February 1, 2021. The formation of the merger made Bank Syariah Indonesia superior in terms of large capital. Competitiveness optimization strategy by taking several steps. First, sharia awareness. BSI KC Pekalongan Pemuda is a media for preaching the concept of Islamic teachings in Sharia banking practices of Openness, Accountability, Professionalism, and Justice. Second, the strategy plan continues to develop to improve it in line with the problems faced by BSI to achieve a competitive advantage. BSI KC Pekalongan Pemuda’s special strategy focuses on commercial patterns in marketing all products by focusing on several agencies such as education centers, health services, offices, and industries to gain a wide network. Third, digitization makes it easy to provide services that only by using a cellphone can be reached easily.